The burden of Parkinson’s disease, 1990–2021: a systematic analysis of the Global Burden of Disease study 2021 - Xi-Chen Wu; Yi-Yue Dong; Yu-Chen Ying; Guang-Yan Chen; Qian Fan; Ping Yin; Yue-Lai Chen (Frontiers in Aging Neuroscience)
BackgroundThe pathogenesis of Parkinson’s disease (PD) remains incompletely understood, has drawn significant attention within the scope of the Global Burden of Disease (GBD) study. Therefore, to explore PD’s global burden and devise countermeasures is indispensable.MethodsData from GBD 2021 to analyze age standardized incidence rate (ASIR), prevalence rate (ASPR), mortality rate (ASMR), and disability adjusted life years (DALYs) rate (ASDR) burden of PD globally. Moreover, the estimated annual percentage change (EAPC) was utilized to gauge PD burden trends from 1990 to 2021. Subsequently, PD burden by sex and 21 GBD regions was further evaluated in 2021. Moreover, the influence of age, sex, and socio-demographic index (SDI) on burden of PD from 1990 to 2021 was examined. Finally, the projection of burden of PD from 2022 to 2026 was also conducted.ResultsFrom 1990 to 2021, ASIR, ASPR, and ASDR were shown to be on an upward trend for both males and females. However, ASMR was higher in males than in females. In addition, ASIR, ASPR, and ASDR in the East Asian region were found to be the highest, and they were higher among males than among females. Notably, with the elapse of years, PD’s total incidence cases, prevalence cases, mortality cases, and DALYs cases were all presented with an upward trend. Moreover, in 1990 and 2021, ASDR in 75–79 age group was the highest. Finally, from 2022 to 2026, PD’s ASIR and ASPR were predicted to exhibit an upward tendency, while ASMR and ASDR were expected to show a downward trend.ConclusionThe research showed a growing global ASIR and ASPR of PD over time, urging more effective health policies to ease its burden.